Akuntansi Zakat Penghasilan pada Organisasi Pengelola Zakat - , ANDI EKO SAPUTRA, Taufikur Rahman S.E., M.B.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aimed to find the right accounting treatment to accommodate the practice of zakat on income. Many practice of zakat on income has been implemented through direct salary deduction mechanism. Apart the fact that it has been controversial, this practice has going on. Aplicated accounting treatment shows that the deduction from salary was being recognized as zakat fund when it was received by zakat organizer organization (amil). I offer critique about this treatment because it doesnât consider the fulfillment of hawl requirement. There will be some unfavorable implication if this treatment is being aplicated. This research was conducted by doing examination of syariâate rules as well as relevant accounting standard (PSAK 109). The result shows that zakat organizer organization need to form a new kind of fund. I propose using the term âzakat savings fundâ for this kind of fund. The deduction from salary will be recognized as zakat savings fund when it was received by zakat organizer organization. Zakat savings fund can be realized as zakat fund if the zakat requirements have been fulfilled. Zakat savings fund is presented separately with another kind of fund. Beside those, there are some information that need to be disclosed on the out-side of the financial statementsâs main body.